Ziarah Kasih Ramadhan 1444H: visitation@Rumah Jagaan Orang Tua Al-Ikhlas, Puchong - UiTM, IPSis (Institut Pengajian Siswazah (IPSis), 2023)
In the month of blessed Ramadan, IPSis successfully held a volunteer program by enlisting senior citizens at “Rumah Jagaan Orang Tua Al- Ikhlas”, Puchong, Selangor. A total of 14 volunteers from IPSis attended the visit to the centre which is occupied by 45 senior citizens including male and female as well as 12 care-taker. The main objective of Ziarah Kasih Ramadhan is to accommodate those who are less attentive to the community. Senior citizens should still be cherished and cared for because they are indeed generations that contribute a lot to our nation and country.